Effect of Sow Intestinal Flora on the Formation of Endometritis - Zhang, Ling; Wang, Linkang; Dai, Yimin; Tao, Tianyu; Wang, Jingqi; Wu, Yunzheng; Zeng, Xiu; Zhang, Jinhua (Frontiers in Veterinary Science, 2021)
Endometritis is the main cause of decreased reproductive performance of sows, while one of the most important factors in the etiology of sow endometritis is aberration of birth canal microbiota. Therefore, people began to pay attention to the structure and composition of the microbiota of the birth canal of sows with endometritis. Interestingly, we found that the risk of endometritis was increased in the sows with constipation in clinical practice, which may imply that the intestinal flora is related to the occurrence of endometritis. Therefore, understanding the relationship between birth canal microbiota and intestinal microbiota of the host has become exceedingly crucial. In this study, the microbiota of birth canal secretions and fresh feces of 4 healthy and 4 endometritis sows were analyzed via sequencing the V3+V4 region of bacterial 16S rDNA gene. The results showed that the significant difference between endometritis and healthy sows birth canal flora in the composition and abundance . Sow endometritis was associated with increasing in the relative abundance of Porphyromonas, Clostridium_sensu_stricto_1, Streptococcus, Fusobacterium, Actinobacillus, and Bacteroides. However, the majority of beneficial bacteria that belonging to Firmicutes phylum (e.g., Lactobacillus and Enterococcus ) declined in endometritis sow. We speculated that some intestinal bacteria (such as Escherichia-Shigella and Bacteroides) may be bound up with the onset of sow endometritis basing on the analysis of intestinal microbiota in sows with endometritis and healthy sows . The above results can supply a theoretical basis to research the pathogenesis of endometritis and help others understand the relationship with the microbiota of sow's birth canal and gut.